Nitric Oxide Levels in Primary Hypertension Patients Receiving Wet Cupping Therapy (Media Kesehatan Masyarakat Indonesia, 2024)
Wet cupping has been shown in several studies to lower blood pressure in hypertensive patients. However, the mechanism of action remains unknown, limiting its use as a complementary non-pharmacological treatment. This study aims to examine the effect of wet cupping on systolic blood pressure, diastolic blood pressure, and nitric oxide levels in hypertensive patients. The study employed a quasi-experimental method with a pretest and post-test design, including a control group. The sample consisted of 40 individuals, they were diagnosed with primary grade I hypertension. The participants were divided into two groups (treatment and control). The intervention group received wet cupping therapy twice, at a 28-day interval, while continuing their antihypertensive medication. The control group only consumed antihypertensive medication. The study revealed a significant decrease in systolic and diastolic blood pressure but no significant increase in nitric oxide levels. After the intervention, the systolic blood pressure in the intervention group decreased by 17.69 mmHg (p=0.010), compared to a decrease of 5.87 mmHg (p=0,108) in the control group, with a difference of (p=0.010). The diastolic blood pressure in the treatment group decreased by 11.56 mmHg (p=0.000), compared to a decrease of 0.73 mmHg (p-0.570) in the control group, with a difference of (p=0.001). The nitric oxide levels in the intervention group increased by 2.5 µmol/L (p=0.530), compared to a decrease of 0.47 µmol/L (p=0.116), in the control group, with a difference of (p=0.539).  It can be concluded that wet cupping therapy reduces systolic and diastolic blood pressure but does not significantly increase nitric oxide levels in the blood of hypertensive patients.
Keywords: Wet cupping; hypertension; nitric oxide; non-pharmacological teraphy; TCM